PLGA/PEG Nanoparticles Loaded with Cyclodextrin-Peganum harmala Alkaloid Complex and Ascorbic Acid with Promising Antimicrobial Activities - Sherif Ashraf Fahmy; Noha Khalil Mahdy; Hadeer Al Mulla; Aliaa Nabil ElMeshad; Marwa Y. Issa; Hassan Mohamed El-Said Azzazy (MDPI AG, 2022)
Antimicrobial drugs face numerous challenges, including drug resistance, systemic toxic effects, and poor bioavailability. To date, treatment choices are limited, which warrants the search for novel potent antivirals, including those extracted from natural products. The seeds of Peganum harmala L. (Zygophyllaceae family) have been reported to have antimicrobial, antifungal, and anticancer activities. In the present study, a 2-hydroxy propyl-β-cyclodextrin (HPβCD)/harmala alkaloid-rich fraction (HARF) host-guest complex was prepared using a thin-film hydration method to improve the water solubility and bioavailability of HARF. The designed complex was then co-encapsulated with ascorbic acid into PLGA nanoparticles coated with polyethylene glycol (HARF-HPßCD/AA@PLGA-PEG NPs) using the W/O/W multiple emulsion-solvent evaporation method. The average particle size, PDI, and zeta potential were 207.90 ± 2.60 nm, 0.17 ± 0.01, and 31.6 ± 0.20 mV, respectively. The entrapment efficiency for HARF was 81.60 ± 1.20% and for ascorbic acid was 88 ± 2.20%. HARF-HPßCD/AA@PLGA-PEG NPs had the highest antibacterial activity against Staphylococcus aureus and Escherichia coli (MIC of 0.025 mg/mL). They also exhibited high selective antiviral activity against the H1N1 influenza virus (IC50 2.7 μg/mL) without affecting the host (MDCK cells). In conclusion, the co-encapsulation of HPCD-HARF complex and ascorbic acid into PLGA-PEG nanoparticles significantly increased the selective H1N1 killing activity with minimum host toxic effects.